Ratiometric imaging of extracellular pH in Streptococcus mutans biofilms exposed to different flow velocities and saliva film thicknesses. Issue 1 (1st January 2021) - Kristensen, Mathilde Frost; Frandsen Lau, Ellen; Schlafer, Sebastian
ABSTRACT: Introduction: Fluid flow has a prominent influence on the metabolism of surface-attached biofilms. Dental biofilms are covered by a thin saliva film that flows at different rates in different locations under stimulated and unstimulated conditions. Methods: The present study employed pH ratiometry to study the impact of different flow velocities, saliva film thicknesses and saliva concentrations on microscale pH developments in S treptococcus mutans biofilms of different age. Results: While saliva flow at a velocity of 0.8 mm/min (unstimulated flow) had little impact on biofilm pH, stimulated flow (8 mm/min; 80 mm/min) affected vertical pH gradients in the biofilms and raised the average pH in 48-h biofilms, but not in 72-h and 168-h biofilms. The saliva film thickness had a strong impact on biofilm pH under both static and dynamic conditions. pH drops were significantly higher in biofilms exposed to a thin saliva film (≤ 50 µm) than a thick saliva film (> 50 µm). pH drops in the biofilms were also strongly dependent on the saliva concentration and thus the buffer capacity of the salivary medium. For 48-h and 72-h biofilms, but not for 168-h biofilms, pH drops in distinct microenvironments were more pronounced when the local biofilm thickness was high.